A pan-cancer analysis reveals the genetic alterations and immunotherapy of Piezo2 in human cancer - Liu, Xin; Jia, Yangpu; Wang, Zhihui; Zhang, Zhaoxiong; Fu, Weihua (Frontiers in Genetics, 2022)
Background: Piezo2 is a transmembrane-spanning ion channel protein implicated in multiple physiological processes, including cell proliferation and angiogenesis in many cell types. However, Piezo2 was recognized as representing a double-edged sword in terms of tumor growth. The prognostic and immunotherapeutic roles of Piezo2 in pan-cancer have not been reported. Methods: In this study, several databases available including the UCSC Xena database, HPA, TIDE, GSEA, and cBioportal were used to investigate the expression, alterations, associations with immune indicators, and prognostic roles of Piezo2 across pan-cancer. R software and Perl scripts were used to process the raw data acquired from the UCSC Xena database. Results: Based on processed data, our results suggested that Piezo2 expression levels were tissue-dependent in different tumor tissues. Meanwhile, the survival analysis reflected that patients suffering from KIRC, LUAD, and USC with high Piezo2 expression had good OS, while those suffering from KIRP and SARC with high Piezo2 expression had poor OS. In addition, our results showed that Piezo2 expression was associated with the infiltration of CD4+ T memory cells, mast cells, and dendritic cells. These results suggested that Piezo2 may involve tumor progression by influencing immune infiltration or regulating immune cell function. Further analysis indicated that Piezo2 could influence TME by regulating T-cell dysfunction. We also found that gene mutation was the most common genetic alteration of Piezo2. The GSEA analysis revealed that Piezo2 was associated with calcium ion transport, the activation of the immune response, antigen processing and presentation pathways. Conclusion: Our study showed the expression and prognostic features of Piezo2 and highlighted its associations with genetic alterations and immune signatures in pan-cancer. Moreover, we provided several novel insights for further research on the therapeutic potential of Piezo2.